“Sastra Populer dan Masalah Mutu Penelitian Sastra di Perguruan Tinggi” - Noor, Redyanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Popular literature is not bad literature, its standard does not lie in its inability to meet the demands of criticism, but on what benefits it gives to the reader. The study of popular literary structures is not important and interesting because the formulas of popular literary structures have definite and consistent criteria. However, popular sociological literary research provides another important and interesting possibility. The sociological facets of popular literature both inside and outside of the text are vast areas of literary research and have a wide range of issues. The production, distribution, and reception aspects are the areas of popular literary research outside the text whose phenomenon is constantly evolving. The social aspect in the text is the area of literary research that has unlimited problems as the object of research material, in line with the productivity of popular literature writing which is very high and fast. Popular literature as an object of research is very rich in materials and data, especially sociological materials and data that are closely related to social issues, both in the text and outside the text. The quality of literary research is actually not determined by the object of research material, but is determined by the formal object and the proper cultivation of its research and the use of appropriate theories and methods so as to produce original, important, and useful findings for the sciences and society.